Overlap Between Apolipoprotein Eε4 Allele and Slowing Gait Results in Cognitive Impairment - Sakurai, Ryota; Watanabe, Yutaka; Osuka, Yosuke; Taniguchi, Yu; Kawai, Hisashi; Kim, Hunkyung; Kitamura, Akihiko; Inagaki, Hiroki; Montero-Odasso, Manuel; Awata, Shuichi; Shinkai, Shoji (Frontiers in Aging Neuroscience, 2019)
Background: Although apolipoprotein E polymorphism ε4 allele (ApoE4) and slow gait are well-known risk factors for cognitive impairment, examination of their combined effect on cognitive function is lacking. Our objective was to elucidate whether a combination of ApoE4 phenotyping and slow gait resulted in greater cognitive impairment. Methods: Overall, 1,085 community-dwelling older adults, either ApoE4 carriers (n = 167, 15.4%) or non-ApoE4 carriers, were included from the “Takashimadaira study.” Gait speed was assessed with an electronic walkway and slow gait was defined as <1 m/s. Cognitive performance was also assessed using the Mini-Mental State Exam (MMSE) and the Trail Making Test (TMT) -A and -B. A two-way analysis of covariance (ANCOVA) (ApoE and gait velocity factors) adjusted for covariates was performed for each analysis. Results: Gait and cognitive performances were similar for ApoE4 and non-ApoE4 carriers. A two-way ANCOVA of the MMSE showed a significant interaction between the two factors. ApoE4 carriers with slow gait had lower MMSE scores than ApoE4 carriers without slow gait and non-ApoE4 carriers with slow gait. Also, a significant main effect of gait velocity on TMT-A was observed, indicating that slow gait is associated with lower scores irrespective of presence of ApoE4. There was no main effect or interaction observed on the TMT-B. Conclusions: Our results suggest that concurrent presence of at least one copy of ApoE4 and slow gait can define a subgroup with the lowest cognition. Elucidating the mechanisms underlying these associations may point out modifiable factors in populations at risk of dementia.